2003
DOI: 10.1038/sj.leu.2403006
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of interferon α and hydroxyurea with hydroxyurea monotherapy in chronic myeloid leukemia (CML-study II): prolongation of survival by the combination of interferon α and hydroxyurea

Abstract: The optimum treatment conditions of interferon (IFN) a therapy in chronic myeloid leukemia (CML) are still controversial. To evaluate the role of hydroxyurea (HU) for the outcome of IFN therapy, we conducted a randomized trial to compare the combination of IFN and HU vs HU monotherapy (CML-study II). From February 1991 to December 1994, 376 patients with newly diagnosed CML in chronic phase were randomized. In all, 340 patients were Ph/BCR-ABL positive and evaluable. Randomization was unbalanced 1:2 in favor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 29 publications
1
37
0
3
Order By: Relevance
“…20,21 The recruited patients represent about 10% of CML patients in Germany (West-Germany until 1990) during the recruitment period. In both trials inclusion criteria were newly diagnosed chronic phase CML, no prior therapy and treatment requirement as defined by the presence of at least one of the following criteria: unexplained fatigue, weight loss of more than 10% body weight in 6 months, fever exceeding 38.51C on five consecutive days, organomegaly-related symptoms, WBC count of more than 50 Â 10 9 /l or platelet count of more than 1 Â 10 12 /l at the time of recruitment.…”
Section: Patients and Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 The recruited patients represent about 10% of CML patients in Germany (West-Germany until 1990) during the recruitment period. In both trials inclusion criteria were newly diagnosed chronic phase CML, no prior therapy and treatment requirement as defined by the presence of at least one of the following criteria: unexplained fatigue, weight loss of more than 10% body weight in 6 months, fever exceeding 38.51C on five consecutive days, organomegaly-related symptoms, WBC count of more than 50 Â 10 9 /l or platelet count of more than 1 Â 10 12 /l at the time of recruitment.…”
Section: Patients and Therapymentioning
confidence: 99%
“…18 Differences in gender-specific incidence and prognosis have long been recognized also in chronic myeloid leukemia (CML). 19 Male predominance was demonstrated in clinical trials, 20,21 and the Sokal score for younger patients (o45 years old) has identified female sex as a favorable prognostic factor. 22 These findings, however, never have been followed up systematically, and gender-associated differences have not been studied well in CML.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10-year survival probability increased from 20 to 53% with previous usually interferon alpha (IFN)-based standard therapy (Hehlmann et al 2003(Hehlmann et al , 2007 to about 90% in the imatinib era (Bjorkholm et al 2011;Hehlmann et al 2011). Given the treatment success and approximately 6000 newly diagnosed patients per year in Europe (Hoffmann et al 2015) and 6600 in the US (Howlader et al 2015) maximizing adherence to promote optimal outcomes is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] The prolongation of survival achieved over the years for the various leukemias by the study groups forming the network are depicted in Figure 3-5. [15][16][17][18] The orientation of the network towards innovation and success makes the network attractive for new participants. The cooperation within the network and the thereby accomplished synergy yield an added value for all network partners.…”
Section: Leukemia Networkmentioning
confidence: 99%